Insecticidal and fungicidal activity of eucalyptol against pest and fungal diseases of soybean - Wagner, Leandro Sebastian; Sequin, Christian J.; Perusset, Sergio Andrés; Fernández, Estrella Natalín; Pretti, Joaquín Ignacio; Campos Soldini, Maria Paula (Ediciones INTA, 2025)
Soybean (Glycine max), a globally significant crop, faces significant economic losses from pests and fungi. Farmers often resort to synthetic pesticides, posing potential risks to human and environmental health. In this context, eucalyptol (1, 8 cineole) stands out in agriculture for its toxicity to various insects and fungi, with minimal environmental and human health impacts. This study aimed to assess in the lab the insecticidal activity of eucalyptol against Spodoptera frugiperda and Epicauta atomaria. Its fungicidal activity was studied against Cercospora kikuchii, C. sojina, and Sclerotium rolfsii. Preliminary exploration of the potential phytotoxic effect on soybean plants has been initiated. Eucalyptol demonstrated significant fumigant insecticidal activity against S. frugiperda 1st instar larvae (LC50 = 9.4 μL/L air) and E. atomaria adults (LC50 = 34.6 μL/L air), along with significant fungicidal activity against C. kikuchii and C. sojina (mycelial inhibition halo diameters of 6.0 and 10.0 mm, respectively, at a concentration of 5 μL/disk). Importantly, eucalyptol exhibited no phytotoxic effects on soybean. Eucalyptol potential as a biopesticide for soybean crops, providing an alternative to synthetic pesticides. Further research is needed to determine its economic viability and large-scale applicability.